2004
DOI: 10.1111/j.1365-2303.2004.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Telecytology in Hokkaido Island, Japan: results of primary telecytodiagnosis of routine cases

Abstract: In 1997, an Internet-based static image telepathology system was built at Sapporo National Hospital, Japan. We can exchange high-resolution microscopical images through a file transfer protocol server and discuss cytological findings and diagnosis on an electronic mailing list. We applied the system to primary telecytodiagnosis. From May 1997 to April 1999 we have made diagnoses of 614 daily cases only by looking at the video monitor images transmitted from the cytotechnologist of Wakkanai Municipal Hospital 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 13 publications
3
47
0
1
Order By: Relevance
“…The diagnostic difficulties and the high interobserver variability in urinary cytology have already been well perceived in previous studies [13,18,39]. Our previous online quiz with 246 participants showed that only 34% of the low-grade and 76% of the high-grade urothelial neoplastic lesions (G3) were concordantly assessed by the participants and that the rate of false diagnoses was also relatively high, even among experienced cytologists [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic difficulties and the high interobserver variability in urinary cytology have already been well perceived in previous studies [13,18,39]. Our previous online quiz with 246 participants showed that only 34% of the low-grade and 76% of the high-grade urothelial neoplastic lesions (G3) were concordantly assessed by the participants and that the rate of false diagnoses was also relatively high, even among experienced cytologists [18].…”
Section: Discussionmentioning
confidence: 99%
“…The latter studies have focused on cervical smears [7,8,9,10,11] or on both gynecological and nongynecological [2] as well as mixed nongynecological cytology [12,13], whereas few have focused on fine-needle aspirations (FNAs) from a single organ like the pancreas [14], thyroid gland [15,16], liver [17] or urinary tract [18]. Most of these studies on telehistology as well as on telecytology report a concordance rate of 80-90% between the diagnoses made on digital images and the reference diagnoses made on the regular glass slides.…”
Section: Introductionmentioning
confidence: 99%
“…These cases were all difficult differential diagnoses, including lymphoma, bile duct and salivary gland neoplasia, in which routine glass slide diagnosis might be fraught with difficulty. The authors conclude that this system worked adequately for routine use [33]. Other examples of static-image cytology have shown excellent accuracy and reproducibility among observers in a variety of organ systems and even for use in veterinary cytology practice [34,35,36,37].…”
Section: Telediagnosis/teleconsultationmentioning
confidence: 99%
“…For a variety of aspiration specimens, Jialdasani et al [32] reported a ‘clinically useful’ diagnosis in 91% of cases using static-image telecytology. Yamashiro et al [33] report on their introduction of a static image-based telecytology system for primary diagnosis in Japan. Over a 2-year period, 614 routine cases were transmitted by cytotechnologists to pathologists working 300 km away, with case discussion simultaneously via e-mail.…”
Section: Telediagnosis/teleconsultationmentioning
confidence: 99%
“…A variety of institutions and practices have described their experience with telepathology in the cytopathology laboratory [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. The aim of this article is to discuss the concepts and goals of telepathology, review the infrastructure necessary for implementation, and cover the necessary validation and regulatory requirements.…”
Section: Introductionmentioning
confidence: 99%